Associations between Depression, Depressive Symptoms, and Incidence of Dementia in Latin America: A 10/66 Dementia Research Group Study - Johansson, Lena (J Alzheimers Dis, 2019)
BACKGROUND: A growing body of evidence suggests that depression is related to dementia in older adults. Previous research has been done in high-income countries and there is a lack of studies in low- and middle income countries (LMICs). OBJECTIVE: To examine the relationship between depressive symptoms and incidence of dementia in a population-based study of older adults in Latin America. METHODS: The study is a part of the 10/66 Dementia Research Group’s population survey and includes 11,472 older adults (baseline mean age 74 years) from Cuba, Dominican Republic, Mexico, Peru, Puerto Rico, and Venezuela. The baseline examinations were done in 2003-2007 and the follow-up examinations 4 years later. Semi-structured psychiatric interviews gave information about ICD-10 depression and sub-syndromal depression (i.e., ≥4 depressive symptoms) at baseline. Information on dementia were collected at the follow-up examination. Competing risk models analyzed the associations between depression and incidence of dementia and the final model were adjusted for age, sex, education, stroke, and diabetes. Separate analyses were conducted for each site and then meta-analyzed by means of fixed effect models. RESULTS: At baseline, the prevalence of depression was 26.0% (n = 2,980): 5.4% had ICD-10 depression and 20.6% sub-syndromal depression. During the follow-up period, 9.3% (n = 862) developed dementia and 14.3% (n = 1,329) deceased. In the pooled analyses, both ICD-10 depression (adjusted sub-hazard ratio (sHR) 1.63, 95% confidence interval (CI) 1.26–2.11) and sub-syndromal depression (adjusted sHR 1.28, 95% CI: 1.09–1.51) were associated with increased incidence of dementia. The Higging I(2) tests showed a moderate heterogeneity across the study sites. CONCLUSION: Our findings suggest that late-life depression is associated with the incidence of dementia in LMICs in Latin America, which support results from earlier studies conducted in high-income countries.